COMPARISON OF LEGAL NORMS AND MECHANISMS FOR SETTLEMENT OF INTER-RELIGIOUS MARRIAGES IN INDONESIA AND SINGAPORE - Istimeisiyah, Dian; Aryanti, Dwi (istinbath, 2025)
Interfaith marriages pose different legal challenges in Indonesia and Singapore, primarily due to differences in validation mechanisms and normative frameworks. This study aims to compare the normative frameworks and resolution mechanisms for interfaith marriages in Indonesia and Singapore. This study uses a normative legal research method, with a comparative approach, to examine regulations, administrative practices, and relevant decisions in both countries. In Indonesia, Article 2, paragraph (1), of the Marriage Law makes religious law the primary requirement for validity, so the state does not provide administrative channels for couples of different religions. This condition is reinforced by Supreme Court Circular Letter No. 2 of 2023, which limits requests for court rulings regarding interfaith marriages. In contrast, Singapore implements a dual legal system for marriage through the Women's Charter and the Administration of Muslim Law Act (AMLA), which allows interfaith marriages among non-Muslims through a defined, structured administrative mechanism. The comparative results show that Indonesia still prioritizes substantive, religion-based norms without administrative resolution mechanisms, while Singapore is more adaptive through its civil marriage regulations, which provide legal certainty. This research emphasizes the need for legal reform in Indonesia to accommodate diversity without neglecting the normative principles held by society.